Will a crude oil price band stabilise the market - Fattouh, B (Oxford Institute for Energy Studies, 2009)
The proposal for a crude oil price band, revived by the Indian delegation during the Jeddah Meeting in July 2008, seems to be gathering support. The French president Nicolas Sarkozy and the UK Prime Minister Gordon Brown urged ‘oil producers to agree a target price range, based on a clearer understanding of the long-term fundamentals’. In a joint article in the Wall Street Journal (8 July 2009), the two leaders gave an indication of what the upper and lower band should reflect, arguing that ‘the world’s economy is still reliant on secure supplies at prices that are not so high as to destroy the prospects of economic growth but not so low as to lead to a slump in investment, as happened in the 1990s’. The proposal for a band for oil prices has also received support from a few oil exporters such as Venezuela. These new calls for a price band represent an underlying change in governments’ views about the process of price formation in oil markets. The sharp rise in oil prices in 2008 has raised concerns about the role of non-fundamental factors (mainly speculative activity in the futures markets) in the determination of the oil price. They have also raised the issue of whether importing and exporting countries have a role in reducing volatility in oil markets. An underlying theme is that oil price volatility is undesirable since it increases uncertainty, which hampers economic growth and undermines investment in the oil sector. Also by increasing uncertainty, volatility in oil prices could derail investment in alternative energy sources. Finally, there are fears that speculative activity can cause oil prices to overshoot and may choke off economic recovery.